Análisis económico financiero y su incidencia en la toma de decisiones operativas de la empresa Zoom Corp SAC años 2017-2018 - Mendoza Villa, Noelia del Rocío (2021)
The present research work has been carried out with the purpose of determining the incidence of a financial economic analysis in the operational decision making of the company Zoom Corp SAC, through this analysis it is proposed to demonstrate that the real situation of the company, the which includes accounts receivable and payable, object of our study; should be taken as a basis for making operational decisions. The research to be developed is of a descriptive-analytical type, since the operational decisions made, the SWOT analysis, the application of financial ratios and analysis to the financial statements are exposed. In addition, there is a direct relationship between the study variables: financial economic analysis and operational decision making. The population of our study is made up of the company Zoom Corp SAC, our sample being the same company in the periods 2017- 2018, where the legal representative provided us with the necessary information to carry out the investigation. The following techniques were used for the development of our study: questionnaire, survey, collection and analysis of information. It was concluded that the financial economic analysis has a positive impact on the operational decision-making of the company Zoom Corp SAC, since it allows us to obtain an accurate diagnosis of the company's situation, within which the status of accounts receivable is detailed. and pay; This diagnosis will serve as a reliable basis, on which to make operational decisions, whose impact will lead to the improvement of these accounts.